Deltamethrin Application on Pre-Weaned Calves Improves Feed Consumption, Stress and Fatigue Status under Heat Stress Conditions - Konstantinos V. Arsenopoulos; Eleftherios Triantafillou; Athanasios I. Gelasakis; Elias Papadopoulos (Pathogens, 2022)
Fly infestation remains a universal problem for dairy cattle herds, affecting the animals’ health and welfare status. Pre-weaned dairy calves are significantly challenged by the direct and indirect consequences of severe fly infestation, heat-stress and their interaction, which contribute to a stressful and fatiguing environment. Among several physiological, behavioral, clinical and biochemical traits, serum cortisol (SC) and creatine kinase (CK) levels, as well as feed consumption can be used as valid indicators of potential stressful and fatiguing conditions and, therefore, can be efficiently used for stress analysis studies. Hence, the objective of the study was to assess the fly-repellency effect of deltamethrin on pre-weaned dairy calves exposed to heat stress conditions, as well as its association with SC, CK concentrations and feed consumption. Two commercial dairy cattle herds of the Holstein breed in Central Macedonia (Greece) were involved in the study during summer months and under heat stress conditions. Deltamethrin administration resulted in (i) a decreased fly population (100% Musca domestica) landing on pre-weaned dairy calves, (ii) a reduced SC (stress indicator) and CK (fatigue indicator) concentration, and (iii) an increased consumption of feedstuff in deltamethrin treated animals compared to the untreated ones.